PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PENERIMA KREDIT PADA BANK RAKYAT INDONESIA UNIT WANEA MANADO - Cynthia . Lintang; Charles R. Ngangi; Melissa Lady G. Tarore; Lorraine W.Th. Sondakh (Universitas Sam Ratulangi, 2013)
AbstrakThe objective of this research is to determine the quality service that influence concerning the satisfaction of credit customer of Bank Rakyat Indonesia Unit Wanea. The research is implemented in Bank Rakyat Indonesia Unit Wanea from September 2012 to November 2012.This research use primary data and secondary data. The Source of primary data is collected from a direct interview with the customer of Bank BRI, based on the listed questions. The source of secondary data is collected from the related intitutions. In this research, the collection of sample uses â€œaccidential samplingâ€ method with a total of 90 interviewed respondents. The research is quantitative so the collected data from the respondents by questioner is appropriate with Likert Scale and is tabulated with multiple linear regression statistical analysis with a computer software. The method and data analysis use descriptive technique analysis method and statistical Inferensial analysis technique.The result of research showed the contribution of service quality Bank Rakyat Indonesia Unit Wanea Manado in form of professionalism and skill (X1), attitude and behavior (X2), accessibility and flexibility (X3), reliability and trustworthiness (X4), reputation and credibility (X5), and servicescape (X6) that simultaneously described the satisfaction of the customers of BRI Unit Wanea in the amount of 62,1 percent. Then from the six variables the most influential variable towards the satisfaction of customers was the reputation and credibility (X5).